Choice sarred songs high voice-Low voice - WILMAS, Wilman (ed.) (Oliver Ditson, 1936)
BARTLETT, J.C. The day is endednCOWLES, Eugene Crossing the barnDEMAREST, Victoria Hymn of the last suppernELLIS, Cecil Seek ye the truth